2017
DOI: 10.21873/anticanres.11400
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin plus Weekly Paclitaxel Combined with Bevacizumab as First-line Treatment for Non-small Cell Lung Cancer

Abstract: Carboplatin plus weekly paclitaxel with bevacizumab was effective and well tolerated by patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, these diagnostic methods provide limited information and are insufficient for an accurate and in depth understanding of the molecular changes taking place during tumor genesis and development (1). Therefore, research into the molecular classification of lung cancer may contribute to more targeted treatments and accurate prognosis (4). The present study revealed that miR-145 expression was downregulated in patients with NSCLC compared with normal healthy volunteers, however there were only a total of six individuals in each group, which is a small sample size and represents a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these diagnostic methods provide limited information and are insufficient for an accurate and in depth understanding of the molecular changes taking place during tumor genesis and development (1). Therefore, research into the molecular classification of lung cancer may contribute to more targeted treatments and accurate prognosis (4). The present study revealed that miR-145 expression was downregulated in patients with NSCLC compared with normal healthy volunteers, however there were only a total of six individuals in each group, which is a small sample size and represents a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular network underlying the development of lung cancer has been partially identified at the protein and gene level. Over the past 10 years, gene therapy based on the underlying molecular network of lung cancer development has advanced, however, the overall 5-year mortality rate for patients with lung cancer has not significantly improved (4).…”
Section: Introductionmentioning
confidence: 99%
“…[70] Bevacizumab is a recombinant, humanised, monoclonal antibody (93% human, 7% murine) that binds all isoforms of circulating VEGF-A, preventing VEGF-A binding to its receptors. Bevacizumab is currently licensed for the treatment of metastatic colorectal cancer, [71] non-small-cell lung carcinoma (NSCLC), [72] glioblastoma multiforme of the brain, [73] metastatic renal cell carcinoma, [74] cervical cancer [75] and ovarian cancer. [76] follow-up.…”
Section: Veg F-a Inhib Iti On a S A Novel S Tr Ategy For The Manag mentioning
confidence: 99%
“…CSP-9 cleaves pro -caspase-3, producing active caspase. Caspases (CSP), like other enzymes, act catalytically, allowing a small number of initiator CSP to activate a large number of effector CSP 53 . The accidental activation of CSP could result in apoptosis, but this is prevented by IAPs 54 .…”
Section: Mtl Dynamics and Cell Cyclementioning
confidence: 99%